1995
DOI: 10.1093/treephys/15.7-8.527
|View full text |Cite
|
Sign up to set email alerts
|

Seed orchards in development

Abstract: This paper reviews the role of seed orchards as output systems for genetic improvement programs. In this paper, technological changes since the 1950s are examined, with emphasis on recent developments. The need to equate the type of seed orchard to the type of forestry practiced is recognized, as is the significance of the relationship between seed orchards and other output systems for genetically improved material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…Despite their success, conventional, wind-pollinated orchards have a few key limitations (Sweet 1995). First, because they are windpollinated, pollen contamination is a problem and intra-orchard mating is uneven.…”
Section: B Seed Orchardsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite their success, conventional, wind-pollinated orchards have a few key limitations (Sweet 1995). First, because they are windpollinated, pollen contamination is a problem and intra-orchard mating is uneven.…”
Section: B Seed Orchardsmentioning
confidence: 99%
“…Finally, because the trees are widely spaced, they require a great deal of land and per-hectare seed yields are low during the early life of the orchard. Because of these limitations, various miniaturized seed orchard designs are being used or considered in Douglas-fir and other species (Sweet 1995;Webber and Painter 1996;Héois 2000).…”
Section: B Seed Orchardsmentioning
confidence: 99%
“…In SO such variability is somewhat larger on the male than on the female side (Kang et al 2003), opposite to what can be observed in natural population (Bilir et al 2004). Some of the problems related to the effective population size and balance of parents in reproduction, can be solved with supplemental mass pollination (Franklin 1971, Sweet 1995 and assisted pollination (Mugnaini et al 2004). …”
Section: Seed Productionmentioning
confidence: 99%
“…This method of regeneration is called "family forestry" (Nikles 1992, Muhs 1993 Boyle et al 1997). In this sense, the SO should ensure the improvement of the quality and quantity of seeds, in comparison to the SS (Sweet 1995), but it contains a limited number of genotypes. The level of improvement is assumed to rise from SS to clonal SO, but simultaneously a decline in genetic diversity may be expected.…”
Section: How Mass Production Of Forest Reproductive Materials Influencmentioning
confidence: 99%
See 1 more Smart Citation